Study of Biodiesel Fuel with Palm Oil and Hydrogen Peroxide Additives - P. P. Oshchepkov; I. A. Zaev; S. V. Smirnov; A. V. Bizhaev (Сельскохозяйственные машины и технологии)
Palm oil is comparable to traditional diesel fuel in terms of calorifi c value, stoichiometric ratio, and cetane number. However, its increased kinematic viscosity and pour point make it diffi cult to use in pure form in diesel engines. (Research purpose) To study specifi c features of burning: diesel fuel with various additives of palm oil (biodiesel fuel); pure 100-percent palm oil; biodiesel fuel with various additives of palm oil and hydrogen peroxide, as well as to develop a method to control its combustion process. (Materials and methods) To determine the ignition time lag, the authors chose a method of kinetic modeling of self-ignition of biodiesel fuel in the air. The self-ignition process was simulated using the Chemical Workbench software package. An adiabatic calorimetric bomb model was used to perform calculations. To describe the process of self-ignition, a universal kinetic mechanism was used, which was verifi ed to calculate self-ignition of diesel and biodiesel fuel surrogates, as well as the formation of toxic substances and soot in the combustion processes. (Results and discussion) It is shown that adding palm oil to diesel fuel increases its ignition time lag, especially at low and medium temperatures of 750-950 kelvin. It was determined that with addition of 10 percent palm oil, the ignition time lag of biodiesel fuel is almost the same as that of diesel fuel no more than 5 percent. Increasing the amount of palm oil additive up to 30 percent and more signifi cantly increases the ignition time lag of the fuel. When using only palm oil as a fuel, the ignition time lag in the temperature range of 800-950 kelvin increases in two times. The study determined the optimal amount of hydrogen peroxide to be used for each composition of biodiesel fuel with various additives of palm oil. (Conclusions) It is shown that additives of hydrogen peroxide can infl uence the reactivity of biodiesel fuel and thereby regulate its ignition time lag.